In-line layer wise measurements for selective laser sintering process - Galovskyi, Bogdan; Hausotte, Tino; Drummer, Dietmar; Harder, Ron (XXI IMEKO World Congress “Measurement in Research and Industry”, 2015)
The popularisation and wider application of the additive manufacturing (AM) has increased quality requirements for this manufacturing process. Reduction of the size and form deviations of manufactured workpieces is one part of quality improvement. In-line optical surface measuring system is considered as the approach for solving the task. Layerwise powder bed surface measurements during the selective laser sintering (SLS) process are aimed to overview each sintered layer (contour of the workpiece) and measure its dimensions. This paper describes the development and practical implementation of the measuring system, as well as a concept for its integration into an SLS machine. Preliminary tests of the measuring system were conducted in real operating conditions.
Keywords: in-line measurements; selective laser sintering; powder bed; stereo vision